2022
DOI: 10.3389/fendo.2022.848715
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota in Children With Hyperuricemia

Abstract: BackgroundIn adults, gut dysbiosis may contribute to the pathogenesis of gout. However, the characteristics of gut microbiota in children with hyperuricemia (HUA) in the absence of clinical gout have not been explored.ObjectiveThis present study analyzed the gut microbiota in children with HUA as compared to controls (Con) and explored bacterial associations that may account for differences.MethodsA total of 80 children were enrolled in this study; they were divided into HUA and Con according to the level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…A cohort study conducted previously found that gout patients had lower levels of the genus Faecalibacterium compared to healthy individuals [40]. Additionally, a case-control study in children showed a negative association between SUA levels and Faecalibacterium abundance [41]. SUA levels are a risk factor for the increased abundance of genus Prevotella9 [42].…”
Section: Discussionmentioning
confidence: 96%
“…A cohort study conducted previously found that gout patients had lower levels of the genus Faecalibacterium compared to healthy individuals [40]. Additionally, a case-control study in children showed a negative association between SUA levels and Faecalibacterium abundance [41]. SUA levels are a risk factor for the increased abundance of genus Prevotella9 [42].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, individuals with hyperuricemia have been found to have decreased microbial diversity and an altered gut microbiota composition compared to those with normouricemia ( 17 ). In children with hyperuricemia, serum uric acid level was positively correlated with genera Actinomyces , Morganella , and Streptococcus , and negatively associated with the short-chain fatty acids-producing bacteria, such as Alistipes , Faecalibacterium, and Oscillospira , and sulfur-producing bacteria Bilophila ( 20 ). Previous studies have shown an association between SUA, gut microbiota, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been studies that have shown that propionic acid and butyric acid [ 44 ] are among the SCFAs that provide ATP to the cells of the intestinal wall, which excretes uric acid [ 45 ]. Acetic acid sodium and butyrate sodium reduce SUA levels in mice, and butyric acid helps maintain intestinal barrier integrity [ 46 ]. Some of the acetic and butyric acids produced in the intestine can enter the body through the bloodstream and be involved in uric acid synthesis and inhibition of XOD activity [ 47 ].…”
Section: Resultsmentioning
confidence: 99%